2017
DOI: 10.1002/mdc3.12469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Determinants of Parkinson's Disease‐associated Pain Using the King's Parkinson's Disease Pain Scale

Abstract: Background: Pain is a frequent feature in Parkinson's disease (PD). Current knowledge on pain and its associated factors in PD has been obtained using nondisease-specific tools. Recently, the King's Parkinson's Disease Pain Scale (KPPS) was published as the first disease-specific scale. The aim of this study was to assess PD-associated pain and its main determinants using the KPPS. Methods: A cross-sectional study was carried out. Consecutive patients with PD were recruited from a movement disorders clinic. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
35
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 34 publications
17
35
3
Order By: Relevance
“…Other authors have reported a much higher prevalence of pain in PD patients ranging from 70.3% to 88.6%. [ 21 22 23 ] Our results are similar to a review of the prevalence of pain among persons with PD, i.e., 59.7%. [ 24 ] Our study results are similar to a systematic review which cited the prevalence of pain 67.6%.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other authors have reported a much higher prevalence of pain in PD patients ranging from 70.3% to 88.6%. [ 21 22 23 ] Our results are similar to a review of the prevalence of pain among persons with PD, i.e., 59.7%. [ 24 ] Our study results are similar to a systematic review which cited the prevalence of pain 67.6%.…”
Section: Discussionsupporting
confidence: 87%
“…KPPS score in our cohort was similar to that in the cohort of 314 PD patients reported by Rodrıguez-Violante et al . [ 22 ] They also observed higher KPPS score in women as compared to men, a finding also reported by other authors. [ 27 28 ]…”
Section: Discussionsupporting
confidence: 77%
“…The results of the present study demonstrate that KPPS-BG had good reliability and validity. Cronbach's α of total scale was 0.75, which indicate good level of internal consistency similar to those reported in the original publication (0.78) [12] and by Rodríguez-Violante et al (0.74) [13], and Soyuer et al (0.827) [20].…”
Section: Discussionsupporting
confidence: 85%
“…Its seven domains include 14 items. KPPS has already been used as a reliable tool available in English language to assess various types of PD-pain [4,13,14,15] and as a secondary outcome in two international multicenter, randomized, controlled trials [16,17]. More recently, the effect of other therapeutic strategies on pain in PD was also assessed by KPPS [18].…”
Section: Introductionmentioning
confidence: 99%
“…Pain is one such non-motor symptom that is present in about two-thirds of PD patients (Defazio et al 2008 ; Broen et al 2012 ), and puts an additional burden on patients’ quality of life (Quittenbaum and Grahn 2004 ; Shibley et al 2008 ; Buhmann et al 2017 ). It has been linked to several clinical factors, such as disease progression (Mylius et al 2011 ), dopaminergic fluctuation (Brefel-Courbon et al 2005 ; Nègre-pagès et al 2008 ; Silva et al 2008 ), depressed mood, and dyskinesias (Rodríguez-Violante 2017 ).…”
Section: Introductionmentioning
confidence: 99%